Customer Satisfaction toward Government Banking Services: A Case Study of RBB Jajarkot Branch - Thapa, Nirmal Kumar; Shahi, Nem Bahadur; Rijal, Jagat Prasad (Karnali Outlook: Knowledge Across Disciplines, 2026)
This study investigates customer satisfaction with government banking services, focusing on the Rastriya Banijya Bank (RBB), Jajarkot Branch in Karnali Province, Nepal. With 350 respondents surveyed using structured questionnaires, the research aims to assess service quality, customer behavior, and the effectiveness of digital banking in a rural context. Key service dimensions such as staff behavior, loan processing, and mobile banking were analyzed. Findings of this study indicates that while most customers are satisfied with staff courtesy and traditional banking services like savings and ATM facilities, significant dissatisfaction exists in areas like digital banking and loan processing due to technical problems, delays of providing services, and communication gaps between bank and customers. Demographic analysis reveals that young, educated users form a majority, yet digital service adoption remains low. The study concludes that improving digital infrastructure, training bank staff, and simplifying loan procedures are essential for enhancing overall satisfaction and strengthening government banks’ role in financial inclusion.